Objective and subjective requirements concerning the introduction of legal custom by a community included in can. 25 CIC - DZIERŻON, GINTER (Prawo Kanoniczne, 2012)
In the presented article, the author focused his attention on the issue of objective and subjective requirements concerning the introduction of legal custom by a community included in can. 25 CIC. He pointed out that the objective condition concerning a community introducing a custom codified in can. 25 CIC should be related not only to communities whose head is an authority holding legislative power but also to communities with executive power only. The author believes that this perception of the law is supported by the introduction into can. 25 CIC of the adverb at least (saltem). Moreover, he is convinced that this thesis is based on ecclesiological premises since according to the contemporary doctrine, the material and formal cause of a custom is a community of the faithful. Another point made by the author is that an intention to introduce a law by a community should be a conscious and the voluntary act a public and habitual nature. It should be made by the majority of the community members in good faith. This means that error diriven actions or thouse made in bad faith do not acquire legal effectiveness.